DAMPAK IMPLEMENTASI VEGETABLE OIL DEVELOPMENT PROJECT (VODP) TERHADAP PENDUDUK DI KALANGALA, UGANDA (2009-2011) - Suci Hafizah Afwan; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research analyzes the impacts of implementation of Vegetable OilDevelopment Project (VODP) to local communities in Kalangala District inUganda. VODP’s main aim is to deduct Uganda’s dependency of import ofvegetable oil by supporting vegetable oil and palm oil production. VODP palm oilsub-project has been implementing in Kalangala, Bugala Island, as one of theefforts of Government of Uganda in reducing rural poverty. This project involvesrole of International Fund for Agricultural Development (IFAD) as loan donorand project supervisor, Wilmar International Ltd, Bidco Uganda Limited (BUL),Oil Palm Uganda Limited (OPUL) as the executors of the project, while thesmallholders are given the chance to participate in the project by selling the freshfruit bunches to BUL. This project binds all actors by applying public-privatepartnership so that they have each profit and risk. However, this research findsout that there are negative impacts in main sectors that is endangeringcommunities’ life in Kalangala.Keywords: Impacts, Partnership, Rural Poverty, Palm Oil Development